Determinants of Patient Loyalty at the Pratama Clinic Kota Tua Padang - Hilda Aripin; Oscar Jayanagara (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
The purpose of this study is to examine direct effect of patient trust and effective physician patient communication to patient loyalty and indirect effect of patient trust, doctor empathy, effective physician patient communication of patient loyalty mediated by patient satisfaction at Kota Tua Padang’s primary health care. This study used a quantitative research design. The data collection technique methods use non-probability sampling with a purposive sampling method. Data was collected through google forms and paper questionnaires distributed directly to 223 respondents BPJS users. The analytical methods used in this study are PLS-SEM. The results of this study show that patient trust, doctor empathy, effective physician patient communication have a positive effect on patient satisfaction; data didn’t confirm that greater patient trust and effective physician patient communication would increase patient loyalty but patient trust, doctor empathy and effective doctor-patient communication have a indirect effect on patient loyalty through the effect on patient satisfaction.